Best Answer

Y = 7 + 2X - 2X^2

set = to 0

7 + 2X - 2X^2 = 0

arrange in standard quadratic form

2X^2 - 2X - 7 = 0

I am too lazy to factor, so the quadratic equation........

-b +/- sqrt(b^2-4ac)/2a

a = 2

b = -2

c = -7

check with discriminant. b^2 - 4ac

-2^2 - 4(2)(-7) = 60; greater than 1; 2 real roots

-(-2) +/- sqrt[(-2)^2 - 4(2)(-7)]/2(2a)

2 +/- sqrt(60)/4

2 +/- 2sqrt(15)/4

not pretty, just, save factoring, exact

Q: What does x equals Y equals 7 plus 2x- 2x squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 52 = 7 2x + 25 = 7 2x = 7 - 25 2x = -18 x = -18/2 x = -9

If x=4 then 2x+7 =

I suggest you use the quadratic formula, with a = 3, b = -2, c = 7.

X=7

-7 +2x = x + 8 2x - x = 7 + 8 x = 15

Related questions

2x + 52 = 7 2x + 25 = 7 2x = 7 - 25 2x = -18 x = -18/2 x = -9

x2 - 2x + 55 = 90x2 - 2x - 35 = 0(x+5)(x-7) = 0x = -5, 7

The slope of the line of 2x plus 2y equals 7 is (7/2x - 1).

2x = -7 - 8y

If x=4 then 2x+7 =

8x-7 plus 2x equals 6 plus 5x plus 2?

I suggest you use the quadratic formula, with a = 3, b = -2, c = 7.

X=7

-7 +2x = x + 8 2x - x = 7 + 8 x = 15

(x - 2)(2x + 7)

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.

If you mean: 2x^2 +9x +7 then it is (2x+7)(x+1) when factored